2020
DOI: 10.1177/1758573220960462
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting biomechanical strength of Latarjet constructs: A systematic review and meta-regression

Abstract: Background The Latarjet procedure reduces recurrent glenohumeral instability but has potential hardware and graft complications. The procedure has been modified to use various screw types as well as suture buttons. Biomechanical studies have evaluated the effect of these implants on construct strength. With varying results it is unclear whether there is an optimal implant to use. Methods We conducted a systematic review of human cadaveric biomechanical studies evaluating Latarjet ultimate failure load. Two ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A recently published systematic review and meta-regression of the biomechanical strength of Latarjet constructs found that each millimeter increase in the screw diameter significantly reduced the ultimate failure load. 25 Alvi et al 1 did not find a significant difference between two 3.5-mm stainless steel cortical screws versus two 4.0-mm stainless steel partially threaded cancellous screws in the final load at failure. Similarly, Shin et al 48 did not find any differences among the screw types tested, all of which consisted of fixation with 2 screws.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…A recently published systematic review and meta-regression of the biomechanical strength of Latarjet constructs found that each millimeter increase in the screw diameter significantly reduced the ultimate failure load. 25 Alvi et al 1 did not find a significant difference between two 3.5-mm stainless steel cortical screws versus two 4.0-mm stainless steel partially threaded cancellous screws in the final load at failure. Similarly, Shin et al 48 did not find any differences among the screw types tested, all of which consisted of fixation with 2 screws.…”
Section: Resultsmentioning
confidence: 93%
“…4,41 In addition, a recent systematic review found that screws produce significantly greater ultimate failure loads than suture buttons when under shear forces. 25 Even though these biomechanical findings may suggest otherwise, clinical studies have reported similar union rates when the 2 constructs are compared, and the same review found suture buttons and screws to be comparable under tensile forces. It is possible that the preservation of bone and maximization of the cancellous contact area with the suture button technique, which may be lost because of greater micromotion, increase union rates.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…6,15,50 Biomechanical investigations in glenohumeral instability models have shown that suture-based bone block fixation is comparable with screw fixation, although the reported stiffness is higher with screw fixation. 29,30,37,41,54 One reported key to stabilize these constructs is reproducible tensioning, which has been clinically reported to improve the bone block healing rate. 10,22…”
mentioning
confidence: 99%
“…6,15,50 Biomechanical investigations in glenohumeral instability models have shown that suture-based bone block fixation is comparable with screw fixation, although the reported stiffness is higher with screw fixation. 29,30,37,41,54 One reported key to stabilize these constructs is reproducible tensioning, which has been clinically reported to improve the bone block healing rate. 10,22 Although suture-based constructs are promising for glenoid reconstruction, there is currently a lack of biomechanical data regarding the initial fixation strength and cyclic contact loading at the graft-glenoid interface after suturebased or screw fixation.…”
mentioning
confidence: 99%